2019
DOI: 10.1016/j.cmi.2018.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial consumption and impact of antimicrobial stewardship programmes in long-term care facilities

Abstract: There is an urgent need for ASPs tailored for LTCFs. Multifaceted organized educational interventions, involving both clinicians and nursing staff, should be advocated and require institutional intervention by health authorities. Future studies assessing the impact of well-defined ASPs in LTCFs should produce compelling evidence in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 64 publications
2
41
2
Order By: Relevance
“…Some countries, such as France, Germany, the Netherlands and Norway, reported the dissemination of national guidelines and Norway and the Netherlands reported that the guidelines were specific for the elderly patient population. The antimicrobial stewardship indicator data in this survey were comparable with that from previous similar surveys, which indicate that improvements in antimicrobial stewardship are urgently needed in LTCFs in the EU/EEA [ 16 , 27 ].…”
Section: Discussionsupporting
confidence: 79%
“…Some countries, such as France, Germany, the Netherlands and Norway, reported the dissemination of national guidelines and Norway and the Netherlands reported that the guidelines were specific for the elderly patient population. The antimicrobial stewardship indicator data in this survey were comparable with that from previous similar surveys, which indicate that improvements in antimicrobial stewardship are urgently needed in LTCFs in the EU/EEA [ 16 , 27 ].…”
Section: Discussionsupporting
confidence: 79%
“…For example, where we found comparable organization of NH care in the selected countries, we know from European studies that there are large differences in Europe regarding what is considered long-term care, which translates into case-mix differences and comparability issues between countries. 4,6 Regarding these differences, a call for more standardized surveillance, definitions, and methods between countries was recently made by the European Society of Clinical Microbiology and Infectious Diseases (ESCMID) Study Group for Infections in the Elderly (ESGIE). 6 Worldwide, transitions in healthcare are occurring or are about to occur as a result of population aging and demographic transition toward older persons.…”
Section: Discussionmentioning
confidence: 99%
“…4,6 Regarding these differences, a call for more standardized surveillance, definitions, and methods between countries was recently made by the European Society of Clinical Microbiology and Infectious Diseases (ESCMID) Study Group for Infections in the Elderly (ESGIE). 6 Worldwide, transitions in healthcare are occurring or are about to occur as a result of population aging and demographic transition toward older persons. 43 A potential pitfall is that these transitions occur at the expense of quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have estimated that between 47% and 70% of residents receive a course of antibiotics annually, and that between 77% to 88% of infections are treated with an antibiotic 7–9. Approximately 50% of these prescriptions are judged to be inappropriate,9 with inappropriate treatment of urinary tract infections and respiratory tract infections common in LTCF residents 7–12. Thus, there is considerable scope for improving antibiotic use in LTCFs.…”
Section: Introductionmentioning
confidence: 99%